Serological and molecular survey of Leptospira spp. among cart horses from an endemic area of human leptospirosis in Curitiba, southern Brazil - Finger, Mariane Angelica; Barros Filho, Ivan Roque de; Leutenegger, Christian; Estrada, Marko; Ullmann, Leila Sabrina [UNESP]; Langoni, Helio [UNESP]; Kikuti, Mariana [UNESP]; Dornbush, Peterson Triches; Deconto, Ivan; Biondo, Alexander Welker (Inst Medicina Tropical Sao Paulo, 2014)
Introduction: Cart horses are a re-emerging population employed to carry recyclable material in cities. Methods: Sixty-two horses were sampled in an endemic area of human leptospirosis. The microscopic agglutination test (MAT) and real-time polymerase chain reaction (qPCR) were performed. Results: A seropositivity of 75.8% with serovar Icterohaemorrhagiae in 80.8% of the horses was observed. Blood and urine were qPCR negative. MAT showed positive correlations with rainfall (p = 0.02) and flooding (p = 0.03). Conclusions: Although horses may be constantly exposed to Leptospira spp. in the environment mostly because of rainfall and flooding, no leptospiremia or leptospiruria were observed in this study.

Introdução: Cavalos carroceiros são uma população reemergente empregada para transportar materiais recicláveis em cidades. Métodos: Em área endêmica para leptospirose humana foram amostrados 62 cavalos. Soroaglutinação microscópica e reação em cadeia da polimerase em tempo real foram empregadas. Resultados: Observou-se soropositividade em 75,8% com sorovar Icterohaemorrhagiae em 80,8% cavalos. Amostras de sangue e urina foram negativas no qPCR. Observou-se correlação positiva entre SAM e pluviosidade (p = 0,02) e alagamentos (p = 0,03). Conclusão: Embora cavalos possam estar constantemente expostos a Leptospira spp. no ambiente, principalmente por chuvas e inundações, leptospiremia e leptospiruria não foram encontradas neste estudo.
Keywords: Leptospira spp.; MAT; qPCR; Horses